Study guides

Q: What is 20 plus x 3 6?

Write your answer...

Submit

Related questions

When x = 3, 3 plus x = 6.

20(x + 3) - (x + 2)(x - 3) After distributing 20 and multiplying (x + 2) and (x - 3) together: 20x + 60 - (x^2 - 3x + 2x - 6) After combining like terms: 20x + 60 - (x^2 - x - 6) After distributing the negative sign to the quantity (x^2 - x - 6): 20x + 60 - x^2 + x + 6 After combining like terms: - x^2 + 21x + 66 Answer: 20(x + 3) - (x + 2)(x - 3) = - x^2 + 21x + 66

To get the answer to this question you would do this: 6-20=14 14+6=20 X=14

9

The answer to 3 plus X plus -7 times 6 equals-38. This is considered to be a math problem.

x+3 = 20 x = 20-3 x = 17

If: x+6 = 3 then the value of x is -3

This formula can be better expressed as [(1+2)(2+3)(3+4)] = (20+x)/2. Simplifying, we get 2[(3)(5)(12)] = 20+x. Then the equation becomes 2[180] = 20+x, or 360 = 20+x. Transferring 20 to the other side, we get 360-20 = x. So, x = 340.

-6 x -3 + (-6) = +18 -6 = +12

6 x (100/3) =200

2x+6 = x+3 the x cancels out the other x x+6=3 subtract 6 from both sides x+6 -6 = 3 -6 x= - 3

There are 3 feet in one yard. Therefore, 6 yards 2 feet is equal to (6 x 3) + 2 = 20 feet.

If you ignore the fact that the question contains the phrase "3 time's 3" which is without any meaning, the answer is 89333197.32.

x=6=x=5+x=13+x=20 x cannot = x+5. This question has no answer.

5X-3 - X-1 + X + 6 The answerdepends on value of X

If: y = x² + 9 and y = 6x + 2 then x² + 9 = 6x + 2 → x² - 6x + 7 = 0 → x = (6 ± √(6² - 4×1))/2 = (6 ± √8)/2 = (6 ± 2√2)/2 = 3 ± √2 Substituting in the second to find the corresponding y: → x = 3 - √2 → y = 6(3 - √2) + 2 = 20 - 6√2 or x = 3 + √2 → y = 6(3 + √2) + 2 = 20 + 6√2 The solution is the two points: (3 - √2, 20 - 6√2) and (3 + √2, 20 + 6√2)

balance the equation 3x-x=20-6 3x-x=2x 20-6=14 2x=14 x=7

x2+x-6 = (x-2)(x+3) when factored

3X + 6 + X = 86 add the like terms, X's, together 4X + 6 = 86 subtract 6 from each side 4X = 80 divide both sides by 4 X = 20 check 3(20) +6 + (20) = 86 86 = 86 checks

(x-2)(x^2+3)

Well, obviously there are no "following statements", but I can tell you that: x+5x-2=18 implies 6x=20 implies x=20/6=10/3 x=10/3 ~ 3.333

(-7 x -3) + (-6) = 21 - 6 = 15

Yes, there are like terms in 3 + 6 + 421 + x. 3, 6, and 421 are all coefficients. Therefore they can be combined to make 430 + x.

x3 + 2x2 + 3x + 6 = x2(x + 2) + 3(x + 2) = (x + 2)(x2 + 3)

x+3/2=3 = x+3=6 = x+3(-3)=6(-3) = x=3